Fibrous materials - Chawla, Krishan K. 1942- (Cambridge University Press, 2016)
This new updated edition provides an unrivaled overview of fibrous materials, their processing, microstructure, properties, and applications. The entire range of fibrous materials is discussed in depth, from natural polymeric fibers such as silk and vegetable fibers, and synthetic polymeric fibers such as aramid and polyethylene, to metallic fibers including steel, tungsten, Nb-Ti, and Nb3Sn, ceramic fibers such as alumina and silicon carbide, and carbon and glass fibers. Fundamental concepts are explained clearly and concisely along with detail on applications in areas including medicine, aerospace, optical communications, and recycling. Significant recent advances are also covered, with new information on the electrospinning of fibers, carbon nanotubes, and photonic bandgap fibers, and detail on advances made in the production and control of microstructure in high stiffness and high strength fibers. Accessibly written and unrivaled in scope, this is an ideal resource for students and researchers in materials science, physics, chemistry, and engineering
Title from publisher's bibliographic system (viewed on 06 Jun 2016)
Keywords: Fibers; Faser; Werkstoffkunde